Skull base reconstruction using hydroxyapatite and nasoseptal flap versus nasoseptal flap alone: meta-analysis and systematic review - Dong-Won Shin; Gi-Taek Yee (Scientific Reports)
Abstract Endoscopic endonasal surgery (EES) is widely employed for interventions in skull base. Despite advancements in surgical techniques, cerebrospinal fluid (CSF) leakage remains a significant concern. The introduction of nasoseptal flap (NSF) dramatically reduced the CSF leakage rates, yet reconstruction techniques continue to vary among institutions and lack standardization. Recently, injectable hydroxyapatite (HA), traditionally used in open skull base reconstruction, has been adapted for use in EES. This study compares the effectiveness of HA and NSF reconstruction with the standard multilayer NSF reconstruction alone. We searched for eligible studies in PubMed, Embase, and Cochrane Library. CSF leakage rates and reconstruction-associated complication rates were thoroughly evaluated. We initially reviewed 3650 records, narrowing down to 13 articles for full-text examination. Of these, 3 retrospective cohort studies met our inclusion criteria, comparing outcomes of HA combined with NSF to NSF alone. The HA plus NSF group tended to exhibit lower rates of CSF leakage compared to the NSF alone group. Similarly, the rate of reconstruction-associated complication was also lower in the HA plus NSF group than in the control group. Skull base reconstruction using HA and NSF can be an effective way to minimize CSF leakage without major complications.